The Art of Research and Scientific Writing in the Clinical Sciences: A Practical Guide - De Jesus, Orlando (Puerto Rico Health Sciences Journal, 2025)
Clinicians have a greater impact in academia when they demonstrate mastery in both clinical and research domains. However, planning a research project and writing a manuscript are among the most intimidating and difficult activities for the clinical faculty. This manuscript aimed to provide a thoughtful and informative description of the fundamental elements of research and essential writing guidelines of a scientific paper. This document was created using personal experiences and literature guides related to research and scientific writing. The article provided stepwise guidelines and pearls to help the clinical faculty, residents, and medical students improve their research and writing skills. This manuscript outlines the essential steps of research and scientific writing. It provides an informative introduction to the fundamental elements of scientific writing guidelines. This initiative is expected to enhance the faculty’s research and writing abilities. At the same time, the information should benefit the residents and medical students with their research projects.